2015
DOI: 10.1039/c5ra09716a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cubane-1,4-dicarboxylate–Zn–Al layered double hydroxide nanohybrid: comparison of structural and optical properties between experimental and calculated results

Abstract: In the present research, we report cubane-1,4-dicarboxylate anions (cuban-dc) assembled into a Zn 2 Al layered double hydroxide (LDH) inorganic host using the coprecipitation method, in which solutions of Zn(II) and Al(III) nitrate salts react with an alkaline solution of cubane-1,4-dicarboxylic acid. Powder X-ray diffraction, FTIR spectroscopy, elemental analyses, and thermal gravimetric analysis (TGA) were used to characterize the successful incorporation of the cubane-1,4-dicarboxylate anions into the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…The LLDPE/OLDHs film with optimal optical properties was OLDHs-6, showing a 5.84% decrease in haze and 1.39% increase in visible light transmittance compared with the pristine LLDPE film. The improved optical properties can be attributed to heterogeneous nucleation induced by the OLDHs nanosheets in the LLDPE matrix, which has previously been observed in other related studies 43 .
Figure 8 Haze and visible light transmittance of OLDHs-0, OLDHs-1, OLDHs-2, OLDHs-4 and OLDHs-6.
…”
Section: Resultssupporting
confidence: 78%
“…The LLDPE/OLDHs film with optimal optical properties was OLDHs-6, showing a 5.84% decrease in haze and 1.39% increase in visible light transmittance compared with the pristine LLDPE film. The improved optical properties can be attributed to heterogeneous nucleation induced by the OLDHs nanosheets in the LLDPE matrix, which has previously been observed in other related studies 43 .
Figure 8 Haze and visible light transmittance of OLDHs-0, OLDHs-1, OLDHs-2, OLDHs-4 and OLDHs-6.
…”
Section: Resultssupporting
confidence: 78%
“…The decomposition temperature of the CNTs is around 550 °C, which indicates that the acid-treated CNTs are thermally stable up to this temperature. LDH-NO3 displays three mass-loss steps [28]: The first one, centered at about 108 °C, is due to the loss of physically adsorbed water and water molecules Figure 2 shows the TGA curves of the LDH in nitrate form, the CNTs and the hybrid LDH-CNTs. The decomposition temperature of the CNTs is around 550 • C, which indicates that the acid-treated CNTs are thermally stable up to this temperature.…”
Section: Methods Of Investigationmentioning
confidence: 99%
“…The decomposition temperature of the CNTs is around 550 • C, which indicates that the acid-treated CNTs are thermally stable up to this temperature. LDH-NO 3 displays three mass-loss steps [28]: The first one, centered at about 108 • C, is due to the loss of physically adsorbed water and water molecules around metal cations, the second one, at about 250 • C, is attributed to the loss of the nitrate anions, and the third one, above 400 • C, due to the de-hydroxylation process. For LDH-CNTs hybrids, three stages of mass loss were also observed in the TG curves.…”
Section: Methods Of Investigationmentioning
confidence: 99%
“…46 Since the molecular dynamic investigation can be used for calculation of the host-guest electrostatic interaction, hydrogen bonding, stability, and diffusion study of the intercalated molecules in the LDH layers, it is preferred to the rst principle study by quantum mechanics (QM) calculation. Also the QM study of the ideal supercell with over 100 atoms, as we have reported in the previous work, 72 is very expensive for the LDHs with large azo molecules. In fact the molecular dynamic simulation aer molecular modeling not only can predict the calculated X-ray diffraction (XRD) pattern for the synthesized LDHs materials, but can also offer layer by layer aggregation with the p-p or dipole-dipole interaction in the gallery of the LDH layer.…”
Section: Photoluminescence Behavior Of Acid Red 27 and The Red 27-zn ...mentioning
confidence: 99%